Benefits of Expressive Writing on Healthcare Workers’ Psychological Adjustment During the COVID-19 Pandemic - Procaccia, Rossella; Segre, Giulia; Tamanza, Giancarlo; Manzoni, Gian Mauro (Frontiers in Psychology, 2021)
COVID-19 outbroke in Wuhan, China, in December 2019 and promptly became a pandemic worldwide, endangering health and life but also causing mild-to-severe psychological distress to lots of people, including healthcare workers (HCWs). Several studies have already showed a high prevalence of depression, anxiety and post-traumatic symptoms in HCWs but less is known about the efficacy of psychological interventions for relieving their mental distress. The aims of this study were: 1) to evaluate the psychological adjustment of Italian HCWs during the COVID-19 pandemic; 2) to investigate the efficacy of an expressive writing intervention, based on Pennebaker’s paradigmatic protocol, on their psychological adjustment; 3) to analyze if outcomes of expressive writing vary in function of individual differences (age, gender, marital status, and baseline values of symptoms). Fifty-five HCWs were randomly assigned to one of two writing conditions: expressive writing (EW, n=30) or neutral writing (NW, n=25). Psychological adjustment (in terms of ptsd, depression and global psychopathology’s symptoms, perceived social support and resilience) was assessed before and after three writing sessions. Participants who received the EW intervention showed higher improvements in ptsd, depression and global psychopathology symptoms. Improvements in EW group varied in function of age, gender, marital status, and baseline values: young, men, married participants and those who had higher baseline scores showed a higher reduction of psychological distress symptoms while women, single and those who had lower baseline value showed increased social support and resilience. In conclusion, the expressive writing intervention had positive effects which varied in function of individual differences on HCWs’ psychological health.